Prevalencia de parásitos gastrointestinales en bovinos criollos de tres tipos de fincas de la comunidad el retorno del barrio las palmas del cantón Pallatanga provincia de Chimborazo. - Cabrera Panata, Yomira Lisbeth (2021)
The present investigation was carried out in the Chimborazo province of the Pallatanga canton of the El Retorno community of three different farms with the aim of establishing the presence of gastrointestinal parasites in cattle, through coproparasitic analysis to structure preventive measures against zoonotic parasitic diseases. , the technique that was put into practice was the flotation with samples of 100 bovine animals that obtained the following results: which were obtained 10 types of parasites which were: Trichuris sp, Strongyloides papillosus, Eimeria bovis, Isospora spp, Eggs cooperia sp, Amoeba cyst, Moniezia expansa, Toxocara vitolorum, Trichostrongylus spp, Taenia spp From a stratum of 100 bovines, 30 came from the Don Eduardo farm where 30 positives were presented with a prevalence of 100%, 30 samples from the Don Humberto Yucailla farm, 22 positive cases were obtained with a prevalence of 73% and in At the Don Humberto Villa farm, 40 samples were obtained, 34 positive cases with a prevalence of 85%. The cattle of the first group <12 months, with a higher value with 7% of Eimeria bovis. The second group of 12-24 months was higher value with 5% of Strongyloides papillosus. In the third group of> 24 months we have two older numbers, the first with 15% of Eimera bovis and the second with 11% of Strongyloides papillous.